Interference-corrected explicitly-correlated second-order perturbation theory - Vogiatzis, Konstantinos D.; Barnes, Ericka C.; Klopper, Wim (Chemical Physics Letters, 2011)
In the complete-basis-set (CBS) model chemistries, an interference correction is added to the total energy. It is added because the CBS-type extrapolation to the basis-set limit of second-order Møller–Plesset (MP2) perturbation theory usually overestimates the magnitude of the basis-set truncation error at higher levels of electron-correlation treatment. In this Letter, the question is pursued whether the CBS-type interference correction could also improve the computational results when the MP2 basis set limit is approached by means of explicitly-correlated MP2 theory using Slater-type geminals.
23 citations (Crossref) [2023-10-31]
Keywords: dept.che